Artificial Intelligence (AI) in Telkom Indonesia's Digital Business Transformation - Acep Arna Hikmat; M Yani Syafei; Umi Narimawati (Electronic Journal of Education, Social Economics and Technology, 2025)
Digital transformation has become the key to organizational success in facing the disruptive era. This study aims to analyze the role of artificial intelligence (AI) in supporting the digital transformation of Telkom Indonesia's business. The research method used is qualitative with in-depth interviews with technology experts and key stakeholders at Telkom Indonesia, especially in mobile network management . The results of the study show that the implementation of AI has increased operational efficiency through network management, especially in better mobile networks, accelerated strategic decision-making and autonomous jobs , and created a positive impact on company performance in the form of efficiency and additional revenue and increased customer satisfaction. With this achievement, AI has proven to be one of the key factors in the success of the company's digital transformation. This study makes a significant contribution to understanding the implementation of AI as the main driver of digital transformation in telecommunications companies such as Telkom Indonesia. These findings are expected to be a reference for technology-based business strategies in the future.